VOF Modeling and Analysis of the Segmented Flow in Y-Shaped Microchannels for Microreactor Systems - Xian Wang; Hiroyuki Hirano; Gongnan Xie; Ding Xu (Advances in High Energy Physics)
Microscaled devices receive great attention in microreactor systems for producing high renewable energy due to higher surface-to-volume, higher transport rates (heat or/and mass transfer rates), and other advantages over conventional-size reactors. In this paper, the two-phase liquid-liquid flow in a microchannel with various Y-shaped junctions has been studied numerically. Two kinds of immiscible liquids were injected into a microchannel from the Y-shaped junctions to generate the segment flow mode. The segment length was studied. The volume of fluid (VOF) method was used to track the liquid-liquid interface and the piecewise-liner interface construction (PLIC) technique was adopted to get a sharp interface. The interfacial tension was simulated with continuum surface force (CSF) model and the wall adhesion boundary condition was taken into consideration. The simulated flow pattern presents consistence with our experimental one. The numerical results show that a segmented flow mode appears in the main channel. Under the same inlet velocities of two liquids, the segment lengths of the two liquids are the same and depend on the inclined angles of two lateral channels. The effect of inlet velocity is studied in a typical T-shaped microchannel. It is found that the ratio between the lengths of two liquids is almost equal to the ratio between their inlet velocities.